Electrocatalytic Water Oxidation at Neutral pH–Deciphering the Rate Constraints for an Amorphous Cobalt‐Phosphate Catalyst System. Issue 46 (13th October 2022) - Liu, Si; Zaharieva, Ivelina; D'Amario, Luca; Mebs, Stefan; Kubella, Paul; Yang, Fan; Beyer, Paul; Haumann, Michael; Dau, Holger
Abstract: The oxygen evolution reaction (OER) is pivotal in sustainable fuel production. Neutral‐pH OER reduces operational risks and enables direct coupling to electrochemical CO2 reduction, but typically is hampered by low current densities. Here, the rate limitations in neutral‐pH OER are clarified. Using cobalt‐based catalyst films and phosphate ions as essential electrolyte bases, current–potential curves are recorded and simulated. Operando X‐ray spectroscopy shows the potential‐dependent structural changes independent of the electrolyte phosphate concentration. Operando Raman spectroscopy uncovers electrolyte acidification at a micrometer distance from the catalyst surface, limiting the Tafel slope regime to low current densities. The electrolyte proton transport is facilitated by diffusion of either phosphate ions (base pathway) or H3 O + ions (water pathway). The water pathway is not associated with an absolute current limit but is energetically inefficient due to the Tafel‐slope increase by 60 mV dec −1, shown by an uncomplicated mathematical model. The base pathway is a specific requirement in neutral‐pH OER and can support high current densities, but only with accelerated buffer‐base diffusion. Catalyst internal phosphate diffusion or other internal transport mechanisms do not limit the current densities. A proof‐of‐principle experiment shows that current densities exceeding 1 A cm −2 can also be achieved in neutral‐pH OER. Abstract : The oxygen evolution reaction (OER) is pivotal in sustainable fuel production. The limiting factors in OER at neutral pH are investigated, which include electrolyte proton transport via a base pathway and a water pathway, as revealed by combining numerical analyses of current‐density–electrode‐potential relations with in situ (operando) X‐ray absorption and Raman spectroscopy.